2022
DOI: 10.1080/15548732.2022.2036294
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal investigation of infants and out-of-home care

Abstract: Foster care placements for infants can be consequential. Research suggests that infants' path through and beyond the care system is different than the experience for children of other age groups. Studying infants is important because of their unique needs for developmentally-sensitive care; because of the underpinnings of attachment theory; and because the longterm impacts of quality care can be pronounced. Prior research examining infants in care has typically focused on their first episode and the outcomes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…Adoption dissolution for very young children is unlikely. In a retrospective study of children placed in care during infancy and followed for 18 years, Magruder and Berrick (2021) found that almost half (46%) left their first episode in care to adoption and 54% were eventually adopted. They estimate that approximately three percent of these children's adoptions dissolved before age 18.…”
Section: Is Adoption Breakdown Common For Former Foster Children?mentioning
confidence: 99%
See 1 more Smart Citation
“…Adoption dissolution for very young children is unlikely. In a retrospective study of children placed in care during infancy and followed for 18 years, Magruder and Berrick (2021) found that almost half (46%) left their first episode in care to adoption and 54% were eventually adopted. They estimate that approximately three percent of these children's adoptions dissolved before age 18.…”
Section: Is Adoption Breakdown Common For Former Foster Children?mentioning
confidence: 99%
“…Although anecdotes from multiple sources and some limited data from previous decades suggest long-term foster care was a pattern for many children (Fanshel, Finch, & Grundy, 1990), efforts to infuse permanency into the terminology, governing policies and practices of child welfare professionals, attorneys, and judicial decision makers appear to have borne fruit. In two recent studies examining the likelihood that an infant placed in care would experience a spell of continuous foster care to age 18, both found that far fewer than one percent of infants experienced a childhood in care (Magruder & Berrick, 2021; Wulczyn, 2020). For children aged 13 or younger, the risk of remaining in foster care to age 18 is less than 10%.…”
Section: Misconceptions To Reconsidermentioning
confidence: 99%
“…In our sample of investigated infants, 98.6% of PSE-identified infants compared to 22.5% of infants without documented PSE were investigated in the first month of life, otherwise known as the neonatal period—a time of tremendous physical vulnerability. A recent longitudinal analysis found that infants reported to CPS as neonates were more likely to experience adoption (Magruder & Berrick, 2022 ). Our results confirm and extend this finding by adding the dimension of PSE, which is often a contributing factor for a neonatal CPS report (Lynch et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%